The Role of Traditional Games in Improving Students’ Physical Literacy in the Modern Era: A Literature Review - Dhiya Naufal Hafiyyan; Sonia Lapesta Nababan; Yonatan Heri Dani Marbun; Derryl Novario Franaditya; Marisa Noviyanti Fajrah Ilsya (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2026)
The modern era, characterized by rapid advances in digital technology, has led to an increase in sedentary lifestyles among children and adolescents, which has resulted in a decline in physical literacy—a crucial foundation for students’ affec-tive, cognitive, and psychomotor development. This study aims to analyze the role of traditional games in improving students’ physical literacy in the modern era through a literature review approach. The method used is a literature review em-ploying descriptive analysis techniques on various relevant articles, journals, and scientific literature. The findings indicate that traditional games such as engklek, gobak sodor, and hide-and-seek have been proven to holistically enhance stu-dents’ physical literacy, encompassing the physical, psychological, social, and cognitive domains. Furthermore, traditional games are effective in reducing sed-entary time, improving motor skills, physical fitness, motivation, and students’ self-confidence to actively engage in long-term physical activities. Traditional games also contribute to character building, the instillation of cooperative values, and the preservation of local culture. Thus, traditional games can serve as a contextual, relevant, and effective pedagogical approach in physical education at school to support the development of physical literacy among students growing up amidst the challenges of the modern era.